Congenital CMV-Associated Hearing Loss: Can Brain Imaging Predict Hearing Outcome?. Issue 2 (3rd March 2021) - Craeghs, Laura; Goderis, Julie; Acke, Frederic; Keymeulen, Annelies; Smets, Koenraad; Van Hoecke, Helen; De Leenheer, Els; Boudewyns, An; Desloovere, Christian; Kuhweide, Rudolf; Muylle, Marie; Royackers, Liesbeth; et al.
Abstract : Objectives: Congenital cytomegalovirus (cCMV) infection is the leading cause of nonhereditary sensorineural hearing loss in childhood and is also associated with CNS abnormalities. The main objective is to investigate the prognostic value of neonatal cranial ultrasound (cUS) and cranial magnetic resonance imaging (cMRI) in predicting long-term hearing outcome in a large cohort of cCMV-infected symptomatic and asymptomatic patients. Design: Data were prospectively collected from a multicentre Flemish registry of children with cCMV infection born between 2007 and 2016. Neonatal cUS and cMRI scans were examined for lesions related to cCMV infection. Audiometric results at different time points were analyzed. The imaging and audiometric results were linked and diagnostic values of cUS and cMRI were calculated for the different hearing outcomes. Results: We were able to include 411 cCMV patients, of whom 40% was considered symptomatic at birth. Cranial ultrasound abnormalities associated with cCMV infection were found in 76 children (22.2% of the cUS scans), whereas cMRI revealed abnormalities in 74 patients (26.9% of the cMRI scans). A significant relation could be found between the presence of cUS or cMRI abnormalities and hearing loss at baseline and last follow-up. Cranial ultrasound and cMRI findings were not significantly correlated with the development of delayed-onset hearing loss. Specificity and sensitivity of an abnormal cUS to predict hearing loss at final follow-up were 84% and 43%, respectively compared with 78% and 39% for cMRI. Normal cUS and cMRI findings have a negative predictive value of 91% and 92%, respectively, for the development of delayed-onset hearing loss. Conclusions: Neuroimaging evidence of CNS involvement in the neonatal period is associated with the presence of hearing loss in children with a cCMV infection. Imaging abnormalities are not predictive for the development of delayed-onset hearing loss.